High density ammonia storage materials - Royse, D; David Royse (2011)
This Thesis considers the use of solid-state metal ammines as ammonia storage materials and endeavours to understand these materials on a fundamental chemical level. The ammines of LiBH₄, MgCl₂, MgBr₂, MgI₂ and Mg(BH₄)₂, are investigated. The structures of lithium borohydride ammines, Li(NH₃)nBH₄ with n = 1, 2, 3 and 4 are solved using X-ray and neutron diffraction, vibrational spectroscopy, nuclear magnetic resonance, and first-principles calculations. The reversibility, bonding and ammonia storage properties of this system are discussed, and investigated using gravimetric analysis and vibrational spectroscopy. The ammines of magnesium halides are investigated using X-ray and neutron powder diffraction, gravimetric techniques, nuclear magnetic resonance, first-principles calculations and vibrational spectroscopy. Their disordered structures, bonding, and decomposition are discussed, and the trends in their properties are used to interpret the properties of other ammines. The ammines of magnesium borohydride are investigated using X-ray and neutron powder diffraction, gravimetric techniques, first-principles calculations and vibrational spectroscopy. The structure, decomposition and reversibility of Mg(NH₃)₆(BH₄)₂ as an ammonia store are presented. Throughout the Thesis and at the end of each Chapter the possibility of using these ammines as solid-state ammonia stores is discussed.